Pope Francis's Effort to Revitalize Catholic Mission - Gregory, William P. (2019)
From the start of his pontificate, Pope Francis has pursued a reform of the Catholic Church aimed at revitalizing Catholic engagement in mission. He has pursued this reform in three areas. He has sought, first, to clarify to all Christians the nature of their task; second, to motivate all Christians to carry out this task; and third, to correct a recurring set of countermissionary attitudes and practices within the church that damage the church's missionary efforts.
Keywords: Catholic theology of mission; Christian discipleship; Pope Francis; church reform; mission spirituality